Validation of a short version of the glaucoma medication self-efficacy questionnaire. Issue 2 (24th May 2011) - Sleath, Betsy; Blalock, Susan J; Stone, Jennifer L; Skinner, Asheley Cockrell; Covert, David; Muir, Kelly; Robin, Alan L
Abstract : Aims: The aims of this study were: (1) to examine whether the original glaucoma medication adherence and eye drop technique self-efficacy scales could be shortened for easier use in practice settings; and (2) to validate these scales against objective medication adherence measures. Methods: Prospective study conducted at a single private practice site. We measured subjects' adherence to glaucoma medications through Medication Event Monitoring System (MEMS) devices and assessed eye drop instillation technique by video-recording. Principal components factor analysis and logistic and linear regression were used to analyse the data. Results: Our results yielded a 10-item Glaucoma Medication Adherence Self-Efficacy Scale that was strongly associated with subject adherence measured using MEMS (β coefficient 8.52, 95% CI 1.94 to 15.1). In addition, the six-item Eye Drop Technique Self-Efficacy Scale was strongly associated with video-recorded subject eye drop installation technique (OR 10.47, 95% CI 1.78 to 61.63). Conclusions: Eye care providers and researchers could use these shorter scales to identify subjects with either poor glaucoma medication adherence and/or eye drop instillation technique. This could help to identify those who may benefit most from education and training on both adherence and eye drop instillation.